Up-to-date Ielts examination highlights - Terence, Martin Renner (Tổng hợp, 2014)
Contents: Model Test 1 Model Test 2 Model Test 3 Model Test 4 Model Test 5 Audio Scripts, Answer Key & Model Answers Model Test 1 Model Test 2 Model Test 3 Model Test 4 Model Test 5